2013
DOI: 10.1038/ncomms3621
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of allosteric interactions among Ca2+-binding sites in a K+ channel RCK domain

Abstract: Ligand binding sites within proteins can interact by allosteric mechanisms to modulate binding affinities and control protein function. Here we present crystal structures of the regulator of K þ conductance (RCK) domain from a K þ channel, MthK, which reveal the structural basis of allosteric coupling between two Ca 2 þ regulatory sites within the domain. Comparison of RCK domain crystal structures in a range of conformations and with different numbers of regulatory Ca 2 þ ions bound, combined with complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Once Ca 2ϩ ions bind to the C1 sites in the N-lobe, a partially activated conformation is stabilized. The increase in calcium concentration leads to Ca 2ϩ binding to the C3 sites in the C-lobe, resulting in complete activation of the RCK domain and maximal stabilization of channel opening (44). In maxi-K ϩ channel, four RCK dimers form a gating ring structure that can expand or constrict (45).…”
Section: Discussionmentioning
confidence: 99%
“…Once Ca 2ϩ ions bind to the C1 sites in the N-lobe, a partially activated conformation is stabilized. The increase in calcium concentration leads to Ca 2ϩ binding to the C3 sites in the C-lobe, resulting in complete activation of the RCK domain and maximal stabilization of channel opening (44). In maxi-K ϩ channel, four RCK dimers form a gating ring structure that can expand or constrict (45).…”
Section: Discussionmentioning
confidence: 99%
“…First, we tested the role of the RCK1 domain in vivo by generating transgenic strains expressing slo-1(RCK1), which contained two mutations (D391A and D396A, equivalent to mouse D362A and D367A, respectively), in a slo-1(null) mutant background. These mutations were previously shown to strongly reduce Ca 2+ sensitivity of the mammalian BK channel and RCK-type domains in other proteins (Cui et al 2009;Smith et al 2013). Two transgenic strains (#1 and #2) were generated to control for variation in transgenesis.…”
Section: Putative Ca 2+ -Sensing Domains In the Worm Bk Channel Are Nmentioning
confidence: 99%
“…This channel was the second K + -selective channel for which a crystal structure was determined (after KcsA). Additional functional and structural studies revealed details of its activation mechanism, including the locations of Ca 2+ -binding sites at the cytosolic side of the channel that contribute to channel activation, as well as kinetic schemes to describe the allosteric mechanism of activation by cytosolic Ca 2+ and inhibition by H + [105, 107, 109, 180182]. …”
Section: Key Questions Subject To Interdisciplinary Study In Ion Tmentioning
confidence: 99%
“…Originally used to characterize ion channels isolated and reconstituted from native tissues, however, planar lipid bilayers are gaining increasing importance in reporting electrical properties of membrane proteins overexpressed and purified from heterologous systems such has bacteria, yeast, or insect cells [95103]. Bilayer recordings typically favor analysis of single ion channels, enabling assessment of scale and duration of individual opening and closing events on microsecond time scales [104109]. …”
Section: Introductionmentioning
confidence: 99%